An Analysis of Women Entrepreneurship: A Case Study of Meerut District - Babita; Rani, Kanchan (Journal of Commerce and Trade, 2022)
Industrial sector plays a vital role in any economy by providing a large number of employment and contributing in the growth and development. The emergence of women entrepreneurs has given rise to an evolving perspective in the field of the entrepreneurship. However, women constitute almost half of the population in the country but their participation in business activities is still very low. They face various gender specific challenges while initiating and operating their enterprise. The present study tried to analyse the socio-economic status of women engaged in enterprenurial activities with the sample size of 30 respondents using convenient sampling in District Meerut, in Uttar Pradesh. The present study is carried out in Meerut District in state Uttar Pradesh. Non-probability sampling is adopted in the present study and basically convenient sampling is conducting during Jan 2022. Women entrepreneurs play an important role in obtaining economic as well as social development. Despite constituting half of the total population in the country women entrepreneurs face numerous challenges while setting up their business. Majority of the women are still unable to get benefits of government support schemes. Women entrepreneurship is a complex domain that requires comprehensive research efforts to decipher its dynamics. Classification-JEL: M21